Social control in the Indigenous Health Care Subsystem: a silenced structure - Scalco, Nayara; Nunes, João Arriscado; Louvison, Marília (Saúde e Sociedade, 2020)
In Brazil, one of the fundamental principles of the Brazilian National Health System is social participation. Through mobilization, indigenous peoples secured the publication of the law establishing the Indigenous Health Subsystem in 1999, structured in 34 Special Indigenous Health Districts. From the beginning, participation instances were organized: Local Councils, District Councils of Indigenous Health (Condisi) and the Condisi Presidents Forum (FPCondisi) This study aims to understand the formal structure and effective configuration of the social participation space of indigenous people in the construction of a differentiated health policy. A qualitative methodology was used with several sources and materials, with documentary analysis of minutes of Condisi Litoral Sul and FPCondisi meetings, legislation and with in-depth interviews with indigenous people and indigenists. The results showed that there are several ways for indigenous people to participate in health policy. It is possible to state that most of the interviewees recognizes Condisi as a space for dialogue between indigenous people and the government, but they also point out the limits of the effectiveness of this and other instances of social control. The silencing of indigenous agendas in formal participation spaces makes these people seek for other ways to lead the construction of a differentiated health policy.